2022
DOI: 10.3390/cancers14194914
|View full text |Cite
|
Sign up to set email alerts
|

Circulating Tumor DNA: Less Invasive, More Representative Method to Unveil the Genomic Landscape of Newly Diagnosed Multiple Myeloma Than Bone Marrow Aspirates

Abstract: Multiple myeloma (MM) is highly heterogenous and dynamic in its genomic abnormalities. Capturing a representative image of these alterations is essential in understanding the molecular pathogenesis and progression of the disease but was limited by single-site invasive bone marrow (BM) biopsy-based genomics studies. We compared the mutational landscapes of circulating tumor DNA (ctDNA) and BM in 82 patients with newly diagnosed MM. A 413-gene panel was used in the sequencing. Our results showed that more than 7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 48 publications
0
8
0
Order By: Relevance
“…There have been few studies that directly compare the disease burden mirrored by CMMCs and cfDNA. Patients with higher molecular tumor burden index levels in ctDNA had higher percentages of CPCs [73]. A comparison of the frequency of MM clones by IGK or IGL rearrangement in cfDNA by NGS and CMMC levels by MFC revealed 80% concordance, and the cell-based approach achieved greater patient coverage than the NGS assay [36].…”
Section: Disease Burden Assessmentmentioning
confidence: 92%
See 4 more Smart Citations
“…There have been few studies that directly compare the disease burden mirrored by CMMCs and cfDNA. Patients with higher molecular tumor burden index levels in ctDNA had higher percentages of CPCs [73]. A comparison of the frequency of MM clones by IGK or IGL rearrangement in cfDNA by NGS and CMMC levels by MFC revealed 80% concordance, and the cell-based approach achieved greater patient coverage than the NGS assay [36].…”
Section: Disease Burden Assessmentmentioning
confidence: 92%
“…However, the ctDNA level only showed a conditional correlation with myeloma cell infiltration in the BM. Although some studies found that patients with a high ctDNA level had more BM infiltrations [47,48,57,73], no quantificational correlation was found between the VAF of tumor-related mutations in cfDNA and BM MM cell infiltration [10], which could be explained by BM heterogeneity and the presence of EM lesions. According to a previous report, patients with short progression-free survival (PFS) and high tumor burden by cfDNA were observed to have inconsistently low BM infiltration.…”
Section: Disease Burden Assessmentmentioning
confidence: 93%
See 3 more Smart Citations